Moderating Effect of Husband’s Controlling Attitudes on the Relation Between Women’s Household Decision-Making Autonomy and Intimate Partner Violence Experience in Nigeria - Sunmola, Adegbenga M. (Journal of interpersonal violence, 2021)
Existing studies show a consensus on the importance of women’s household decision-making autonomy. However, the studies also show mixed findings of the association between the variable and intimate partner violence (IPV). In this study, moderating effects of husband’s controlling and domineering attitudes on the association between women’s household decision-making autonomy and husband-perpetrated physical, sexual, and emotional violence were investigated. Data used in the study were drawn from an existing database of a 2013 cross-sectional Demographic and Health Survey (DHS) of nationally representative sample (N = 19,360) of Nigerian married women. Participants were interviewed on measures of women’s autonomy, husband’s attitudes, and husband-perpetrated violence. Results revealed that women who exercised high household decision-making autonomy significantly experienced more physical (b = .31, t = 11.78, p < .001), sexual (b = .05, t = 3.59, p < .01), and emotional (b = .17, t = 9.76, p < .001) violence if they reported relationship with husbands who endorsed high controlling and domineering attitudes. The results represent an extension over existing research and have implications on how husband’s attitudes could improve women’s autonomy and reduce their IPV experience in various intervention settings.